2020
DOI: 10.1016/j.molliq.2019.111746
|View full text |Cite
|
Sign up to set email alerts
|

Connecting precursors to a protic ionic liquid: Effects of hydrogen bond synergy in acid-base binary mixtures on the solvent-solute interactions

Abstract: How does the solvation behaviour of a protic ionic liquid (PIL) relate to their precursor Brønsted acid and base? By studying how the solvent-solute interactions in a binary mixture of a Brønsted acid and base changes with respect to composition, a rational connection between precursor and PIL can be made. Using acetic acid and N,N-dimethylethanolamine as model precursors, we demonstrate here that the change in solvent-solute interactions, as inferred from the Kamlet-Taft solvatochromic parameters, are drastic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 65 publications
(72 reference statements)
0
6
0
Order By: Relevance
“…One potential solution to antisolvent separation from a PIL may lie in exploiting the nature of PILs as binary mixtures of a Brønsted acid and base. We have recently shown that changing the stoichiometry in a binary mixture of acetic acid and N,N-dimethylethanolamine has a profound effect on the apparent solvent-solute interactions (Reid et al 2019). Applying that same methodology to the system of propionic acid (HOPr) and 1,1,3,3-tetramethylguanidine (TMG), we show how changing the composition can lead to an increase in cellulose solubility, as well as a means of regenerating cellulose from solution without the need of a dedicated antisolvent.…”
Section: Introductionmentioning
confidence: 99%
“…One potential solution to antisolvent separation from a PIL may lie in exploiting the nature of PILs as binary mixtures of a Brønsted acid and base. We have recently shown that changing the stoichiometry in a binary mixture of acetic acid and N,N-dimethylethanolamine has a profound effect on the apparent solvent-solute interactions (Reid et al 2019). Applying that same methodology to the system of propionic acid (HOPr) and 1,1,3,3-tetramethylguanidine (TMG), we show how changing the composition can lead to an increase in cellulose solubility, as well as a means of regenerating cellulose from solution without the need of a dedicated antisolvent.…”
Section: Introductionmentioning
confidence: 99%
“…Once confirmed, the peaks that were unique to the PILs were then identified within the biomass-PIL mixture that was produced (according to the in situ PIL synthesis method S3). This will aid in confirming the formation of the PIL and validate this new PIL synthesis method for effective synthesis in several applications. , …”
Section: Resultsmentioning
confidence: 84%
“…This will aid in confirming the formation of the PIL and validate this new PIL synthesis method for effective synthesis in several applications. 28,29 Figure 3 shows the absorption spectra in the 1100−1900 cm −1 range of pure PILs (i.e., 5/5 ratio) along with the analogous solutions with varying molar ratios. The molecular and ionic species are separately observed in the IR spectroscopy, indicating the existence of a chemical equilibrium.…”
Section: Three Of the Pretreatment Solvents [Eth][oac]mentioning
confidence: 99%
“…Reid et al measured Kamlet–Taft solvatochromic parameters for acetic acid and N , N -dimethylethanolamine, across compositional range. 55 The studied mixtures had β-hydrogen bond basicities varying across a wide range, both above and below the values measured for the starting materials, demonstrating the value of exploring such PILs as tuneable solvents.…”
Section: Introductionmentioning
confidence: 84%
“…What is important from the applications viewpoint is that each acid-base composition is a distinctive PIL, with a unique set of properties, which can be fine-tuned to suit an application, adding an additional degree of freedom in the design of ILs. 55 In carboxylic acid PILs, the preference for hydrogenbonded, acid-rich networks may be so strong that excess base is phase-separated from the mixture, particularly in the case of ternary amines, devoid of hydrogen-bond-donating {N-H} motifs. In-depth studies show that the two phases are: an acid-rich PIL on the bottom, and a phase containing mainly the amine (or very base-rich PIL) on top.…”
Section: Key Fundamental Aspects Protic Ionic Liquidsmentioning
confidence: 99%